Australia : Report on the Observance of Standards and Codes (ROSC)-Summary Assessments. (IMF Staff Country Reports; Country Report ;, 2012)
The main objective of the assessment was to analyze and observe the implementation of the International Organization of Securities Commissions (IOSCO) Principles in Australia. The various responsibilities of the Australian Securities and Investments Commission (ASIC) were highlighted and the flaws identified. It was noted that the ASIC underwent a major structural reorganization and modified its policies as a response to the initial IOSCO assessment conducted in 2006. The Australian legal and regulatory framework for securities markets largely corresponded with the principles of IOSCO.